ORGANIZACIÓN CONTABLE EN LA EMPRESA COMERCIAL “MAXCOLOR” DE LA CIUDAD DE LOJA, PERIODO DEL 01 DE JULIO AL 31 DE DICIEMBRE DEL 2019. - Iñiguez Lozano, July Narcisa (2021)
The thesis called “ACCOUNTING ORGANIZATION OF THE“ MAXCOLOR ”COMMERCIAL COMPANY OF THE CITY OF LOJA, PERIOD JULY 01 TO DECEMBER 31, 2019” is aimed at organizing an accounting process, in order to know the economic and financial situation of the company in study. It allows to fulfill the general objective: "Organize commercial accounting in the company" MAXCOLOR "of the city of Loja, period July 1 to December 31, 2019", and the specific objectives: "Prepare a plan and manual of accounts in function of the needs and policies of the company "MAXCOLOR" as a basis for the development and application of its accounting organization "; "Design auxiliary records in order to consolidate and support the information recorded in the main records"; "Develop the accounting process from the initial inventory, until the presentation of the financial statements in the period from July 1 to December 31, 2019" and "Apply the basic financial indicators used in the commercial sector, in order to determine the financial economic reality ”, beginning the presentation of theoretical foundations related to the subject. The accounting process began, and concludes with the presentation of financial statements, in addition, the evaluation of the statements is carried out with the application of financial indicators, which give us a general perspective of the economic-financial information that the company is going through. and timely and reliable data was obtained, reflected in the Financial Statements, where a net profit for the year of $ 34,198.63 was determined; an asset of $ 237,904.19; a liability of $ 38,338.21 and equity of $ 200,754.18, significant information for its owner and based on this, make appropriate decisions for the economic growth of the commercial company.